2020
DOI: 10.1002/agj2.20363
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of smallholder farming systems in Africa

Abstract: This forum paper provides a synthesis and discussion of 14 categories of lessons learned from experiences for achieving farm-level impact with smallholder farmers in Africa. These lessons were reported in a symposium hosted by the Agronomy in Africa community of the American Society of Agronomy. The lessons, listed in order of frequency of reporting, were the need to: have adequate infrastructure and services; enable spontaneous adoption; have multidisciplinary and institutional collaboration; build on previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Results from field research during the past 35 yr compiled in a published dataset (Wortmann, 2020) were analyzed for UTS and LTS (Figure 1). The highland and semiarid agricultural lands of SSA were excluded from this analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Results from field research during the past 35 yr compiled in a published dataset (Wortmann, 2020) were analyzed for UTS and LTS (Figure 1). The highland and semiarid agricultural lands of SSA were excluded from this analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The yield response data were from trials conducted since 1985 as reported in a database of >6,100 georeferenced response functions with citations (Wortmann, 2020). These functions were standardized according to yield (Mg ha −1 ) = a − bc r where a was yield at the plateau for the particular nutrient application, b was the maximum increase in yield due to the nutrient application, c (<1.0) was a determinant of the response curve shape, and r was the nutrient application rate (Jansen et al., 2013).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Major farming system changes are driven by sufficient profit potential with acceptable risk and manageable financial investment (Wortmann et al, 2020). The profit potential may be partly due to improved net returns on investment in annual crop production or improved fodder production.…”
Section: Ley/fallow Rotation Globallymentioning
confidence: 99%
“…However, many management options for sustainable intensification are knowledge intensive and require expensive external inputs, making them out of reach for many smallholder farmers. Moreover, riskiness, labour shortage and limited benefits that can be accrued from small farms reduce the adoption potential of sustainable intensification options for smallholder farmers (Giller, 2020;Hazell et al, 2010;Wortmann et al, 2020). Hence, for a large part of the population, livelihood improvement through sustainable intensification is beyond reach (e.g.…”
Section: Introductionmentioning
confidence: 99%